2021
DOI: 10.1001/jamaoto.2021.1259
|View full text |Cite
|
Sign up to set email alerts
|

Association of COVID-19 Vaccination and Facial Nerve Palsy

Abstract: IMPORTANCE Peripheral facial nerve (Bell) palsy has been reported and widely suggested as a possible adverse effect of the BNT162b2 (Pfizer-BioNTech) COVID-19 vaccine. Israel is currently the leading country in vaccination rates per capita, exclusively using the BNT162b2 vaccine, and all residents of Israel are obligatory members of a national digital health registry system. These factors enable early analysis of adverse events.OBJECTIVE To examine whether the BNT162b2 vaccine is associated with an increased r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
112
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(122 citation statements)
references
References 11 publications
0
112
1
Order By: Relevance
“… A case report of possible uveitis post-vaccination BNT162b2 2 3 days Reduction in visual acuity, visual distortion n = 1 Shemer et al . 41 Association of COVID-19 Vaccination and Facial Nerve Palsy: A Case-Control Study A case-control study of association between facial nerve palsy between vaccinated and unvaccinated groups BNT162b2 1, 2 9–14 days n = 21 Vera-Lastra et al . 42 Two Cases of Graves’ Disease Following SARS-CoV-2 Vaccination: An Autoimmune/Inflammatory Syndrome Induced by Adjuvants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… A case report of possible uveitis post-vaccination BNT162b2 2 3 days Reduction in visual acuity, visual distortion n = 1 Shemer et al . 41 Association of COVID-19 Vaccination and Facial Nerve Palsy: A Case-Control Study A case-control study of association between facial nerve palsy between vaccinated and unvaccinated groups BNT162b2 1, 2 9–14 days n = 21 Vera-Lastra et al . 42 Two Cases of Graves’ Disease Following SARS-CoV-2 Vaccination: An Autoimmune/Inflammatory Syndrome Induced by Adjuvants.…”
Section: Resultsmentioning
confidence: 99%
“… 38 provided detailed expositions of the signs and symptoms that led to a diagnosis of Bell’s palsy in COVID-19 BNT162b2 vaccine recipients. An Israeli case-control study 41 found that 21 of 37 individuals (56.8%) with facial nerve palsy were recently vaccinated with the first or second dose of the BNT162b2 vaccine, compared with 44 of 74 (59.5%) in the control group. After adjustment for pre-existing immune- or inflammatory-related disorders, diabetes, and a previous episode of peripheral nerve palsy, odds ratio (OR) for exposure to the vaccine among cases was insignificant at 0.84 (95%CI 0.37–1.90, p -value = 0.67).…”
Section: Resultsmentioning
confidence: 99%
“…Bell’s palsy developed within 2 weeks following first dose of COVID-19 vaccination. There was no difference in any of the clinical parameter between vaccinated or unvaccinated groups [ 97 ].…”
Section: Arterial Eventsmentioning
confidence: 99%
“…They also compared the numbers of cases in January and February 2021 to the same period during 2015 to 2020, and found no meaningful increase in admission numbers due to facial nerve palsy. [57] Renoud et al conducted a disproportionality analysis using the World Health Organization’s pharmacovigilance database. They found no higher safety signal for facial palsy after mRNA Covid-19 vaccines when compared with all other viral vaccines or restricted to influenza vaccines.…”
Section: Discussionmentioning
confidence: 99%